'Among his fellows cast': A histotaphonomic investigation into the impact of the Black Death in England. (October 2021) - Hemer, Katie A.; Booth, Thomas J.; Raffone, Caterina; Mann, Colleen; Corkhill, Claire L.; Willmott, Hugh
Highlights: The Black Death had a devastating impact on 14th-century populations in England. Bone diagenesis identified the early taphonomic histories of the plague dead. Different strategies were employed to deal with variable volumes of plague dead. Lime may have been used in the funerary rites of three high-status individuals. Abstract: The Black Death had a devastating impact on communities living in Europe during the mid-14th century. The devastation wreaked by the epidemic was thought to lead to the disruption of social norms, including those surrounding the burial of the dead. Some scholars have, however, suggested this was not always the case, in particular for those communities living in rural settings (Kacki et al., 2011). Recent excavation at Thornton Abbey in Lincolnshire revealed two burial populations; one associated with the abbey's medieval hospital, and the other a mass grave that was in use during the Black Death epidemic. Together with the mass grave and post-epidemic burials from East Smithfield, London, these two populations presented an opportunity to explore the early taphonomic histories of the plague dead through the inspection of bone diagenesis associated with bacterial soft tissue decomposition. The histological analysis of 81 skeletons revealed striking differences in the post-mortem treatment of the plague dead in rural Lincolnshire compared to those buried in urban London, and in this paper we explore the possible scenarios that may account for this variability. We also present three cases where the individuals' status in life may have led to attempts at inhibiting their corporeal decay.